Metipranolol promotes structure and function of retinal photoreceptors in the rd10 mouse model of human retinitis pigmentosa. Issue 2 (3rd December 2018) - Kanan, Yogita; Khan, Mahmood; Lorenc, Valeria E.; Long, Da; Chadha, Rishi; Sciamanna, Jason; Green, Ken; Campochiaro, Peter A.
Abstract: Metipranolol is a β‐adrenergic receptor antagonist that is given orally for the treatment of hypertension and also applied topically to the cornea for treating glaucoma. It also inhibits nitrosative stress which has previously been shown to be the cause of cone photoreceptor death in retinitis pigmentosa. In this study, we tested the hypothesis that metipranolol protects photoreceptor structure and function in the mouse model rd10 . At P35, compared with vehicle‐treated rd10 mice in which rod degeneration was nearly complete, rd10 mice given daily subcutaneous injections of 40 mg/kg of metipranolol had reduction in markers of nitrosative stress, fewer TUNEL‐positive cells, increased outer nuclear layer thickness, and substantially more staining for rhodopsin. This was accompanied by significantly higher mean scotopic and photopic electroretinogram b‐wave amplitudes indicating improved photoreceptor function. At P50, metipranolol‐treated rd10 mice had decreased 3‐nitrotyrosine staining in the retina, increased immunostaining for cone arrestin, a marker for cone photoreceptors, and significantly higher scotopic and photopic b‐wave amplitudes at the highest stimulus intensity compared with vehicle‐treated mice. At P65, cone density was significantly higher in metipranolol‐treated versus vehicle‐injected rd10 mice. Metipranolol applied as eye drops promoted cone photoreceptor function in retinas of rd10 mice greater than subcutaneously injected metipranolol. The reduced nitrosative damage and rescue of functional loss of photoreceptors in rd10 mice suggests that metipranolol, a drug with established ocular safety and tolerability, may have potential for treating patients with retinitis pigmentosa. Abstract : In retinitis pigmentosa (RP), rods die from mutations, causing oxygen levels to increase in the retina. This leads to the activation of NADPH oxidase and production of an excess of superoxide radicals. These radicals interact with nitric oxide to produce toxic peroxynitrites which decomposes into toxic nitrites and nitrates which are harmful to the cones, leading to cone death. Metipranolol inhibits the production of these nitrites and nitrates and protects cones from cell death, making it a promising drug to protect cones in RP.